Design of Sand Smoothing Tool With Anthropometry Approach to Improve Productivity at CV Karya Gemilang Teknik - Bintang Kharisma Ramadhan; Handy Febri Satoto (Telkom University, 2025)
The efficiency of the silica sand refining process significantly affects the quality of metal casting at CV Karya Gemilang Teknik, Sidoarjo. Currently, the company performs sand refinement manually, which leads to excessive processing time, inconsistent results, and operator fatigue. This study aims to design an ergonomic sand-refining machine using an anthropometric approach to improve both operator comfort and production productivity. A combination of field observation, anthropometric data collection, ergonomic design analysis, and prototype testing was employed. The key anthropometric parameters considered were standing shoulder height and arm reach, analyzed using statistical measures such as mean, standard deviation, and percentile. Based on these results, the optimal machine dimensions were determined at a height of 92.27 cm and a width of 67.5 cm to accommodate the majority of workers. The designed machine applies a hammer mill mechanism with a 1 HP electric motor, steel frame, and V-belt transmission system. Experimental results indicate that the new design significantly reduces sand-refining time, enhances operator posture and comfort, and produces finer and more uniform sand particles. Consequently, the proposed ergonomic design contributes to improved efficiency, consistent product quality, and higher productivity in the casting process at CV Karya Gemilang Teknik